Cardiorenal protection with SGLT2: Lessons from the cardiovascular outcome trials. Issue 4 (11th December 2019) - Silva‐Cardoso, José; Sheikh, Omar; Nashawi, Mouhamed; Pham, Son; Gallegos, Kelly M.; Dinkha, Laith R.; Chilton, Robert J.
Abstract: Sodium glucose cotransporter 2 (SGLT2) inhibitors are a class of drugs that were primarily developed for the treatment of type 2 diabetes mellitus. However, these agents have shown to provide additional beneficial effects. We will discuss three main topics regarding the use of SGLT2 inhibitors: noncardiovascular effects, cardiovascular benefits, and novel clinical indications. Multiple clinical trials and preliminary studies across varying disciplines have shown that these agents exhibit cardiorenal‐protective benefits, retinoprotective benefits, and may aid in weight loss without causing marked hypoglycemia. Therefore, these agents represent an avenue in clinical practice to manage comorbid conditions in the hyperglycemic patient. Because of their multifaceted effects and robust action, SGLT2 inhibitors represent therapy options for providers that not only provide beneficial clinical results but also reduce total patient drug burden. Abstract : Highlights SGLT2 inhibitors represent a novel class of anti‐hyperglycemic drugs with benefits that extend beyond glycemic control. The novel mechanism of action of these drugs have shown to have differential benefit in patients with diabetic nephropathy, cardiovascular disease risk reduction, and retinoprotective effects as established by clinical trials. Given the findings compiled via literature review, these drugs promise hope for patients seeking to manage their, as well as providers wishing to integrate their use in their practice. 摘要: 钠‐葡萄糖协同转运蛋白‐2(SGLT2)抑制剂是一类主要用于治疗2型糖尿病的药物。然而, 这些制剂已经显示额外的益处。我们将讨论有关SGLT2抑制剂使用的三个主要方向:非心血管效果、心血管益处和新的临床适应症。跨学科的多项临床试验和初步研究表明, 这些药物显示出保护心肾以及视网膜的好处, 并可能有助于减肥, 而且不会导致明显的低血糖。因此, 这些药物代表了临床实践中管理高血糖患者共存疾病的一条途径。由于SGLT2抑制剂的多方面效应和强大的作用, SGLT2抑制剂提供了新的治疗选项, 不仅有好的临床结果, 而且减少了患者的总药物负担。